Calcule o valor de cada função abaixo nos pontos - 2, - 1, 2 e 3.
A)
![f(x) = 7 {}^{x} f(x) = 7 {}^{x}](https://tex.z-dn.net/?f=f%28x%29+%3D+7+%7B%7D%5E%7Bx%7D+)
B)
![g(x) = 18 \times ( \frac{1}{3} ) {}^{x} g(x) = 18 \times ( \frac{1}{3} ) {}^{x}](https://tex.z-dn.net/?f=g%28x%29+%3D+18+%5Ctimes+%28+%5Cfrac%7B1%7D%7B3%7D+%29+%7B%7D%5E%7Bx%7D+)
C)
![h(x) = \frac{4}{3} {}^{x} h(x) = \frac{4}{3} {}^{x}](https://tex.z-dn.net/?f=h%28x%29+%3D+%5Cfrac%7B4%7D%7B3%7D+%7B%7D%5E%7Bx%7D+)
D)
![i(x) = ( \frac{1}{4} ) {}^{x} + 2 i(x) = ( \frac{1}{4} ) {}^{x} + 2](https://tex.z-dn.net/?f=i%28x%29+%3D+%28+%5Cfrac%7B1%7D%7B4%7D+%29+%7B%7D%5E%7Bx%7D+%2B+2)
E)
![j(x) = ( \frac{2}{5} ) {}^{x} + \frac{3}{5} j(x) = ( \frac{2}{5} ) {}^{x} + \frac{3}{5}](https://tex.z-dn.net/?f=j%28x%29+%3D+%28+%5Cfrac%7B2%7D%7B5%7D+%29+%7B%7D%5E%7Bx%7D+%2B+%5Cfrac%7B3%7D%7B5%7D+)
F)
![k(x) = (27 \frac{1}{3}) {}^{x} k(x) = (27 \frac{1}{3}) {}^{x}](https://tex.z-dn.net/?f=k%28x%29+%3D+%2827+%5Cfrac%7B1%7D%7B3%7D%29+%7B%7D%5E%7Bx%7D+)
Soluções para a tarefa
f(-2) = 7^-2
f(-2) = 1/7^2
f(-2) = 1/49
f(-1) = 7^-1
f(-1) = 1/7
f(2) = 7^2
f(2) = 49
f(3) = 7^3
f(3) = 343
B)
g(-2) = 18 x (1/3)^-2
g(-2) = 18 x 3^2
g(-2) = 18 x 9
g(-2) = 162
g(-1) = 18 x (1/3)^-1
g(-1) = 18 x 3
g(-1) = 54
g(2) = 18 x (1/3)^2
g(2) = 18 x 1/9
g(2) = 18/9
g(2) = 2
g(3) = 18 x (1/3)^3
g(3) = 18 x 1/27
g(3) = 18/27
g(3) = 2/3
C)
h(-2) = (4/3)^-2
h(-2) = (3/4)^2
h(-2) = 9/16
h(-1) = (4/3)^-1
h(-1) = 3/4
h(2) = (4/3)^2
h(2) = 16/3
h(2) = 8
h(3) = (4/3)^3
h(3) = 48/27
h(3) = 16/9
D)
i(-2) = (1/4)^-2 + 2
i(-2) = 4^2 + 2
i(-2) = 16 + 2
i(-2) = 18
i(-1) = (1/4)^-1 + 2
i(-1) = 4 + 2
i(-1) = 6
i(2) = (1/4)^2 + 2
i(2) = 1/16 + 2
i(2) = 1/16 + 32/16
i(2) = 33/16
i(3) = (1/4)^3 + 2
i(3) = (1/4)^3 + 2
i(3) = 1/64 + 2
i(3) = 1/64 + 128/64
i(3) = 129/64
E)
j(-2) = (2/5)^-2 + 3/5
j(-2) = (5/2)^2 + 3/5
j(-2) = 25/4 + 3/5
j(-2) = 125/20 + 12/20
j(-2) = 137/20
j(-1) = (2/5)^-1 + 3/5
j(-1) = 5/2 + 3/5
j(-1) = 25/10 + 6/10
j(-1) = 31/10
j(2) = (2/5)^2 + 3/5
j(2) = 4/25 + 3/5
j(2) = 4/25 + 15/25
j(2) = 20/25
j(2) = 4/5
j(3) = (2/5)^3 + 3/5
j(3) = 8/125 + 3/5
j(3) = 8/125 + 75/125
j(3) = 83/125
k(-2) = (27 x 1/3) ^-2
k(-2) = 27^-2 x (1/3)^-2
k(-2) = 1/27^2 x 3/1^2
k(-2) = 1/729 x 9/1
k(-2) = 9/729
k(-2) = 1/81
k(-1) = (27)^-1 x (1/3)^-1
k(-1) = 1/27 x 3/1
k(-1) = 3/27
k(-1) = 1/9
k(2) = (27)^2 x (1/3)^2
k(2) = 729 x 1/9
k(2) = 729/9
k(2) = 81
k(3) = (27)^3 x (1/3)^3
k(3) = 19.683 x 1/27
k(3) = 19683/27
k(3) = 729
Explicação passo-a-passo:
A)
f(-2) = 7^-2
f(-2) = 1/7^2
f(-2) = 1/49
f(-1) = 7^-1
f(-1) = 1/7
f(2) = 7^2
f(2)=49
f(3) = 7^3
f(3) = 343
B)
g(-2) = 18 x (1/3)^-2
g(-2) = 18 x 3^2
g(-2) = 18 x 9
g(-2) = 162
g(-1) = 18 x (1/3)^-1
g(-1) = 18 x 3
g(-1) = 54
g(2) = 18 x (1/3)^2
g(2) = 18 x 1/9
g(2) = 18/9
g(2) = 2
g(3) = 18 x (1/3)^3
g(3) = 18 x 1/27
g(3) = 18/27
g(3) = 2/3
C)
h(-2) = (4/3)^-2
h(-2) = (3/4)^2
h(-2) = 9/16
h(-1) = (4/3)^-1
h(-1) = 3/4
h(2) = (4/3)^2
h(2) = 16/3
h(2) = 8
h(3) = (4/3)^3
h(3) = 48/27
h(3)=16/9
D)
i(-2) = (1/4)^-2 + 2
i(-2) = 4^2 + 2
i(-2) = 16 + 2
i(-2) = 18
i(-1) = (1/4)^-1 + 2
i(-1) = 4 + 2
i(-1) = 6
i(2) = (1/4)^2 + 2
i(2) = 1/16 + 2
i(2) = 1/16 + 32/16
i(2) = 33/16
i(3) = (1/4)^3 + 2
i(3) = (1/4)^3 + 2
i(3) = 1/64 + 2
i(3) = 1/64 + 128/64
i(3) = 129/64
E)
j(-2) = (2/5)^-2 + 3/5
j(-2) = (5/2)^2 + 3/5
j(-2) = 25/4 + 3/5
j(-2) = 125/20 + 12/20
j(-2) = 137/20
j(-1) = (2/5)^-1 + 3/5
j(-1) = 5/2 + 3/5
j(-1) = 25/10 + 6/10
j(-1) = 31/10
j(2) = (2/5)^2 + 3/5
j(2) = 4/25 + 3/5
j(2) = 4/25 + 15/25
j(2) = 20/25
j(2) = 4/5
j(3) = (2/5)^3 + 3/5
j(3) = 8/125 + 3/5
j(3) = 8/125 + 75/125
j(3) = 83/125
F)
k(-2) = (27 x 1/3) ^-2
k(-2) = 27^-2 x (1/3)^-2
k(-2) = 1/27^2 x 3/1^2
k(-2) = 1/729 x 9/1
k(-2) = 9/729
k(-2) = 1/81
k(-1) = (27)^-1 x (1/3)^-1
k(-1) = 1/27 x 3/1
k(-1) = 3/27
k(-1)=1/9
k(2) = (27)^2 x (1/3)^2
k(2) = 729 x 1/9
k(2) = 729/9
k(2) = 81
k(3) = (27)^3 x (1/3)^3
k(3) = 19.683 x 1/27
k(3) = 19683/27
k(3) = 729